Transit of Venus poetry exchange Venustransit-Lyrik-Austausch - Baker, Hinemoana 1968-; Baker, Hinemoana 1968-; Colquhoun, Glenn; Kolbe, Uwe 1957-; Oleschinski, Brigitte 1955-; Price, Chris 1962-; Sandig, Ulrike Almut 1979- (Victoria University Press, 2016)
"The Transit of Venus on 6 June 2012 was the inspiration for an international, multi-layered poetry project. New Zealand's status as the Guest Country of Honour at the 2012 Frankfurt Book Fair was a good opportunity to realise it. In June of that year the German poets Uwe Kolbe, Brigitte Oleschinski and Ulrike Almut Sandig visited Uawa/Tolaga Bay on New Zealand's East Coast to experience the transit with the New Zealand poets Hinemoana Baker, Glenn Colquhoun and Chris Price and to condense their experiences into poetry. In October the New Zealand poets travelled to Germany to meet their German colleagues in a translation workshop, 'VERSchmuggel / reVERSible', at the Berlin literaturwerkstatt. After translating a selection of one another's poems, the poets performed them in Berlin and at the Hamburg Museum of Ethnology, and finally the project, the poets and the translations were presented at the Frankfurt Book Fair"...Publisher information